X-ray polarization spectroscopy from ultra-intense interactions - Booth, N; Clarke, R; Gallegos, P; Gizzi, L; Gregori, G; Koester, P; Labate, L; Levato, T; Li, B; Makita, M; Pasley, J; Rajeev, P; et al. (2010)
Detailed knowledge of fast electron energy transport following the interaction of ultrashort intense laser pulses is a key subject for fast ignition. This is a problem relevant to many areas of laser-plasma physics with particular importance to fast ignition and X-ray secondary source development, necessary for the development of large-scale facilities such as HiPER and ELI. Operating two orthogonal crystal spectrometers set at Bragg angles close to 45° determines the X-ray s- and p- polarization ratio. From this ratio, it is possible to infer the velocity distribution function of the fast electron beam within the dense plasma. We report on results of polarization measurements at high density for sulphur and nickel buried layer targets in the high intensity range of 1019 - 1021 Wcm-2. We observe at 45° the Ly-α doublet using two sets of orthogonal highly-orientated pyrolytic graphite (HOPG) crystals set in 1st order for sulphur and 3rd order for nickel. © 2010 IOP Publishing Ltd.